Resistance to thyroid hormone due to a novel mutation in the thyroid beta receptor (THRβ) gene coexisting with autoimmune thyroid disease—A case report - Skowrońska-Jóźwiak, Elżbieta; Gach, Agnieszka; Cyniak-Magierska, Anna; Nykel, Anna; Jurkowska, Monika; Lewiński, Andrzej (Frontiers in Genetics, 2023)
Resistance to thyroid hormone (RTH) is a syndrome characterized by impaired responsiveness of target tissues to thyroid hormones. The relationship between RTH and thyroid autoimmunity is still unknown. We demonstrate a case report of a woman with a novel mutation of THRB gene coexisting with autoimmune thyroid disease (AITD). A 36-year-old woman has been treated since childhood for a thyroid disease. The patient had increased concentrations of thyroperoxidase and thyroglobulin antibodies (TPOAb, TgAb). Based on high levels of thyroid hormones (TH), she received unnecessary - as it turned out later - long-term treatment with methimazole and finally – she underwent subtotal thyroidectomy. After the surgery her TSH remained significantly elevated, despite the treatment with 150 µg L-thyroxine and 15 µg L-triiodothyronine daily. A sequence analysis of the THRB gene revealed a novel dinucleotide substitution affecting codon 453, resulting in the replacement of the normal proline with an asparagine (c.1357_1358delinsAA, p.(Pro453Asn)). The mutation has not been described in the literature yet, however THRB codon 453 represents a mutational hot spot, frequently altered in the TH receptor ß gene. After establishing the diagnosis of RTH, the patient has been treated with 300 µg L-thyroxine daily, with clinical improvement and normalization of TSH. The coexistence of RTH and AITD may additionally impede establishing of a proper diagnosis, leading to unnecessary therapy and delaying correct treatment. The presented case encourages a closer cooperation between clinical endocrinologists and geneticists.